ANALISIS PENGARUH SUHU UDARA, CURAH HUJAN, KELEMBABAN UDARA DAN KECEPATAN ANGIN TERHADAP ARAH PENYEBARAN DAN AKUMULASI PARTICULATE MATTER (PM10): STUDI KASUS KOTA PEKANBARU - Muhaniroh Muhaniroh; Riad Syech (Komunikasi Fisika Indonesia, 2021)
Forest fires in Riau Province are the biggest contributor to air pollution that spreads to the urben area of Pekanbaru. PM10 is one of the most dangerous elements contained in forest fire smoke. This study aims to map areas that have accumulated the spread of PM10 in the city of Pekanbaru. This research has been carried out using a data interpretation methodology using data on the value of PM10, rainfall, air temperature, humidity, wind direction and wind speed in the form of monthly data from 2015 – 2019. Data processing is carried out using Microsoft office excel 2017, SPSS, surfer 17, google earth pro. The result of the analysis there is a significant effect of wearther parameters on PM10. Wind speed has a strong influence on the spread of PM10. Mapping of wind distribution patterns and distribution patters of PM10 in sub-district Limapuluh every year and the wind direction accoriding to the wrplot flower chart always goes to sub-direction Limapuluh.